Anti‐sarcopenic effects of diamino‐diphenyl sulfone observed in elderly female leprosy survivors: a cross‐sectional study. Issue 3 (15th October 2015) - Lee, Sang Yoon; Kim, Won; Park, Hee‐Won; Park, Sang Chul; Kim, In Kwon; Chung, Sun G.
Abstract: Background: It has been reported that 4, 4′‐diamino‐diphenyl sulfone (DDS), the longtime treatment of choice for leprosy, prolongs the lifespan and increases mobility in animal models by reducing the levels of reactive oxygen species and inhibiting muscle pyruvate kinase activity. This study aimed to investigate whether sarcopenic status in leprosy survivors was influenced by recent history of DDS medication. Methods: Forty‐one elderly female leprosy survivors were recruited. The DDS group was defined as survivors who had been taking the drug for the past year or more. Body composition measured by dual energy X‐ray absorptiometry, limb muscle strength, short physical performance battery, and International Physical Activity Questionnaire in Korean were compared. Results: The DDS group tended to have higher skeletal muscle mass index (24.4 ± 2.7 vs. 22.6 ± 2.2%, P = 0.066) and regional skeletal muscle mass index in non‐dominant leg (8.9 ± 1.0 vs. 7.9 ± 0.9%, P = 0.018) than those of the control group although they had significantly worse leprosy disability than the control group ( P = 0.027). The DDS group had greater strength than the control group in non‐dominant shoulder abductor, elbow flexor, hip flexor, and knee extensor ( P = 0.005, P = 0.029, P = 0.021, and P = 0.002, respectively). Weekly walking amount was significantly longer ( P = 0.020) in the DDS group than the control group. The total lifetime DDS exposure significantly correlated with skeletal muscle mass of the lower extremity in non‐dominant leg ( r = 0.379, P = 0.015). Conclusions: DDS‐taking leprosy survivors had larger skeletal muscle mass and greater muscle strength over non‐taking survivors. There was a dose–response relationship between total lifetime DDS exposure and skeletal muscle mass of lower extremity. These findings might suggest potential anti‐sarcopenic effects of DDS.